Together forever [large type] - Hedlund, Jody (Hedlund, Jody. Orphan train., 2018)
Marianne Neumann takes a job as a placing agent with the Children's Aid Society in hopes of finding her younger sister. In 1858 New York she finds it's not always easy to offer children a better life.